Primary Tumor Site Affects Survival in Patients with Gastroenteropancreatic and Neuroendocrine Liver Metastases. (12th March 2019) - Tierney, John F.; Poirier, Jennifer; Chivukula, Sitaram; Pappas, Sam G.; Hertl, Martin; Schadde, Erik; Keutgen, Xavier
Abstract : Background . Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are commonly present with metastatic disease, and the liver is the most frequent metastatic site. Herein, we studied whether primary tumor site affects survival in patients with GEP-NETs and liver metastases (NELM). As a secondary endpoint, we studied whether extrahepatic disease and surgical resection impact survival in this patient population. Methods . Patients with NELM diagnosed from 2006 to 2014 were identified from the National Cancer Database. Kaplan-Meier curves and nested Cox proportional hazards were used to assess variables associated with survival. Results . 2947 patients with well- or moderately differentiated GEP-NETs and NELM met the inclusion criteria for this study. Patients with small bowel NETs survived the longest of all GEP-NETs with NELM (median not reached). Rectal and gastric NETs with NELM had the shortest survival (median 31 months). Patients with extrahepatic metastases who underwent any operation survived longer than those managed nonoperatively (median survival 38.7 months vs. 18.6 months, p = 0.01 ). On multivariable analysis, operations on the primary tumor and distant metastatic site (HR 0.23-0.43 vs. no surgery), treatment at an academic/research hospital, Charlson comorbidity index of 0, no extrahepatic metastases, and younger age were associated with prolonged survival (p < 0.01 ). Conclusions . Primary tumor site affects survival in patients with GEP-NETs and NELM. Surgical resection seems beneficial for all GEP-NETs with NELM, even in the presence of extrahepatic metastases.